Catalytic hydrodechlorination of 2-chlorophenol using viral-templated palladium nanoparticles. - St. John, Peter Corbin. (Tufts Archival Research Center, 2005)
Chlorinated hydrocarbons are of particular environmental concern due to their toxicity in small quantities and usage in several industrial applications. 2-Chlorophenol is one type of chlorinated hydrocarbon which is used as a pesticide to prevent microbial growth in several industries, including oils, adhesives, textiles, and pharmaceuticals. Current methods of removal either rely on activated charcoal absorption techniques, or use air stripping to force the volatile contaminants into the atmosphere where they are degraded. Both methods are costly and particularly wasteful. Thus, there is an urgent need for robust, inexpensive catalysts for hydrodechlorination reactions which could be used at the industrial scale. Recent investigations have demonstrated the effectiveness of nanoscale palladium at catalyzing the hydrodechlorination of similar contaminates, but cost and stability constraints have prevented their widespread use. This study investigates the catalytic properties of palladium nanoparticles reduced onto genetically modified Tobacco Mosaic Virus nanotemplates. The TMV were self-assembled into high surface area scaffolds on gold chips, and were then coated with palladium using aqueous palladium ions in a reducing sodium hypophosphite solution. The resulting chips were analyzed by atomic force microscopy to determine the surface topology. The chips were placed in a hydrodechlorination reactor with a dilute 2-chlorophenol solution and a constant hydrogen sparge, and the products were analyzed by high performance liquid chromatography (HPLC). The results show that air stripping due to the hydrogen sparge significantly reduces the chlorophenol concentrations in the reactor and inhibits kinetic investigations. Deactivation studies suggest that the catalyst retains its form after reaction, but further analysis is needed.